2012
DOI: 10.5402/2012/725203
|View full text |Cite
|
Sign up to set email alerts
|

Coloration of Anuran Tadpoles (Amphibia): Development, Dynamics, Function, and Hypotheses

Abstract: Colorations of anuran tadpoles surely function in many of the same ways that have been ascribed to color and pattern in other animals, but the paucity of data forces one to look to other groups to generate hypotheses. Such an action often occurs because of the difficulty of defining specific fitness parameters to larval forms. The commonly muted colorations of tadpoles are typically considered to function only in some form of crypsis, but we discuss other functions in the particular context of behavioral ecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 173 publications
(177 reference statements)
0
35
0
Order By: Relevance
“…Although coloration can vary according to pond conditions, predator density, and ontogeny (Thibaudeau and Altig, 2012), we observed that living and fixed B. flavopicta tadpoles in all development stages do not exhibit black dots (melanophores) distributed along the body surface, as observed in most tadpoles in the B. pseudopseudis group (see Fig. 5 for B. itapoty and B. oxente tadpoles) except B. ibitiguara and B. saxicola (Cardoso, 1983;Eterovick and Brandão, 2001).…”
Section: Discussionmentioning
confidence: 80%
“…Although coloration can vary according to pond conditions, predator density, and ontogeny (Thibaudeau and Altig, 2012), we observed that living and fixed B. flavopicta tadpoles in all development stages do not exhibit black dots (melanophores) distributed along the body surface, as observed in most tadpoles in the B. pseudopseudis group (see Fig. 5 for B. itapoty and B. oxente tadpoles) except B. ibitiguara and B. saxicola (Cardoso, 1983;Eterovick and Brandão, 2001).…”
Section: Discussionmentioning
confidence: 80%
“…, the light absorbing organelles) can be reallocated in the melanophores ( i.e. , a type of pigment cells within the dermal chromatophore unit), resulting in a lightening (pigment aggregation) or darkening (pigment dispersion) of the skin323334353637. Although these colour shifts are not instantaneous as those exhibited by chameleons, flatfish or cephalopods383940, both larvae and adults of many amphibian species benefit from relatively rapid ( i.e.…”
mentioning
confidence: 99%
“…The vast majority of studies on amphibian camouflage have focused on anurans283334375960 (see ref. 61 for an extensive review), whereas the adaptive value of cryptic coloration and behaviour of salamanders –aside from their aposematic traits626364– has received considerably less investigation.…”
mentioning
confidence: 99%
“…Cott, ; Fogden & Fogden, ; Rudh & Qvarnström, ; Arbuckle & Speed, ). In tadpoles, body coloration serves many functions, such as crypsis, thermoregulation, ultraviolet protection and communication (Thibaudeau & Altig, ). Diversity of coloration in tadpoles is not limited to genetic variation among species or populations, but may also be a product of plasticity and environmentally induced changes resulting from ecological conditions such as light regimes, turbidity, coloration of the environment (water or background), the presence of predators, temperature and UV‐B radiation (Rudh & Qvarnstöm, ).…”
mentioning
confidence: 99%
“…Diversity of coloration in tadpoles is not limited to genetic variation among species or populations, but may also be a product of plasticity and environmentally induced changes resulting from ecological conditions such as light regimes, turbidity, coloration of the environment (water or background), the presence of predators, temperature and UV‐B radiation (Rudh & Qvarnstöm, ). For instance, tadpoles inhabiting turbid water often look pale, while conspecifics living in tannin‐stained water are frequently brightly coloured (Thibaudeau & Altig, ). In response to predator presence, coloration may change to either enhance background matching, improve camouflage through disruptive coloration (Polo‐Cavia & Gomez‐Mestre, ), or promote bright colours on expendable body parts in order to lure predators away from vital areas (Touchon & Warkentin, ).…”
mentioning
confidence: 99%